Using teacher-designed materials in teaching ESP vocabulary to the second-year students of Fashion Designing at National University of Art Education: Difficulties and solutions - Trinh, Thi Thu Hien (ĐHNN, 2017)
PART I: INTRODUCTION...PART II: DEVELOPMENT. PART III: CONCLUSION